Searching for market-based sustainability pathways: Challenges and opportunities for seafood certification programs in Japan. (February 2017) - Swartz, Wilf; Schiller, Laurenne; Rashid Sumaila, U.; Ota, Yoshitaka
Abstract: Over the past two decades, there has been a proliferation of consumer-facing, market-based initiatives for marine conservation—most notably in seafood eco-labels and sustainability certifications. Yet, despite the growing recognition of these initiatives by consumers and retailers in North America and Europe and the (subsequent) acceptance of their role in seafood distribution by fisheries and fish marketing industries around the world, seafood certification programs have thus far made little progress in Japan. Here, the evolution of the three seafood eco-label and certification programs in Japan is examined and insights into the ongoing challenges they face in terms of the domestic supply chain network, consumer preference and their social-cultural attitude toward sustainability are provided. Despite an initial lack of success, seafood certification programs in Japan can be useful in enhancing consumer awareness for fisheries resource conservation and identifying Japanese domestic small-scale fisheries that are already engaged in sustainable fishing practices. A possible pathway for developing an eco-certification program suitable for the Japanese seafood market is provided through integration of environmental and cultural sustainability under the existing certification framework. Highlights: No seafood eco-certification programs have successfully captured the Japanese market and this is due to the structural mismatch in the certification schemes and Japanese domestic fisheries and seafood supply chains. Integration of environmental and cultural sustainability, with participation from domestic coastal fisheries, is essential for eco-certification programs in Japan to capture national interest.